(untitled) (Journal of International Crisis and Risk Communication Research, 2020)
In 2016, the University of Kentucky became embroiled in an open records debate with its student newspaper, The Kentucky Kernel. Following a professor’s resignation amid a sexual misconduct investigation, the Kernel asked for records pertaining to the case.The University refused, claiming the information would violate survivors’ privacy. The decision sparked public backlash, forcing the University to combat accusations that it was prioritizing reputation over student safety. This case study provides insight into the crisis management process by exploring how key actors in the case made decisions. Drawing from theoretical perspectives including stakeholder theory and the ethics of care and justice, this study explores the complexities of addressing incongruent stakeholder perspectives and balancing stakeholder interests, along with offering implications for public relations practitioners.